ION SOURCE FOR A SINGLE PARTICLE ACCELERATOR - Tomas Matlocha (Acta Polytechnica CTU Proceedings)
This paper proposes a method to obtain very low beam current on the injection side of an particle accelerator. By using a combination of a well known ion source type and a short photo-emissive laser pulse, very low amount of ions can be created. The method could be used in the ion source of various types of the accelerators, where very low beam current is essential. The design is adapted to build a compact internal ion source and the dimensions of the device are adjusted to fit central region of the cyclotron U-120M. The functional parameters of the device are discussed and the ammount of the produced ions is estimated.